Just cause and gross misconduct: The dismissal itinerary - Bravo Montalvo, Washington Luis (2019)
Just cause and gross misconduct constitute two major concepts that a regular employee usually associates with dismissal and, at the same time, with arbitrariness and abuse. This is not always so, given that the only possibility in Peru to dismiss an employee, at least in theory, is his dismissal for a just cause, that is, in accordance with the law. This article analyzes the treatment of these concepts regulated by Supreme Executive Order No. 003-97-TR, Consolidated Text of Legislative Executive Order No. 728 and the manner how the case law has gradually shaped and consolidated their scope, an evolution that has not, albeit, removed the idea of the arbitrary dismissal from the labor spectrum, has allowed us to understand it from two valuable perspectives: the improvement of the quality of the service that must be inherent to an employment contract or relationship and respect for the quality of the employee and the right to work.